DISAIN SISTEM SCADA DI INSTALASI PENGOLAHAN AIR BERSIH UNTUK KEBUTUHAN DOMESTIK DI SUATU KAWASAN INDUSTRI - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2008)
Industrial area represents location where some industries operate in one same area region. Usually an industrial area besides there are factory also there are office and housing. To fulfill domestic clean water required by housing and office, usually the organizer of industrial area have developed a Water Treatment Plant (WTP) with source of raw water which come from a river emitting a stream of around area. The increasing of domestic clean water needs has pushed management to increase the production of clean water by the existing WTP. Besides that, to increase the quality of clean water service to the domestic exist in industrial area, hence felt important to develop a system of SCADA to manage existing process in the WTP. As step early is to identify and plan the design system of SCADA for domestic WTP. From the result of development planning, the SCADA can be developed step by step according to the project plan and existing budget.Ã‚Â Kata kunci : Water Treatment Plant (WTP), Instalasi Pengolahan Air (IPA), Kebutuhan Air Bersih Domestik Perumahan, Supervisory Control And Data Acquisition (SCADA).